Henning Larsen (1999)
Información gráfica de la ampliación de la Gliptoteca Ny Carisberg, Copenaghen, 1996.
Keywords: DINAMARCA; KØBENHAVN; COPENHAGUE; MUSEOS DE ARTE; MUSEOS; AMPLIACION; CONCURSOS; PREMIOS; LARSEN, HENNING